The Modified Quadruple-Tanks Process: A Flexible Mathematical Model with an Adjustable Simulink Block - Numsomran, A.; Chaoraingern, J.; Trisuwannawat, T. (My University, 2014)
This paper presents the modified quadruple-tanks process, a flexible laboratory process with an adjustable Simulink block, which is multivariable system consisting of four interconnected water tanks included with lower interacting valve. The new general form of modified quadruple-tanks mathematic model and Simulink block is developed for the advantage of control system analysis and design which can make practical use for many styles of multivariable process by adjusting the value of connected valve resistance, inlet and outlet valve ratio. In this paper described clearly about physical properties of modified quadruple-tanks process, mathematical modeling, transformation of modified quadruple-tanks process, analysis of right half-plane zeros characteristic and controller design for multivariable system. By the several models of transformed modified quadruple-tanks, they can be used to teach students in the skills of multivariable control system analysis and design, understanding control limitation due to interactions, model uncertainties, non-minimum phase behavior, and unpredictable time variations, design decentralized controllers, Implementing decouples to reduce the effect of interactions, and understanding their limitations. © (2014) Trans Tech Publications, Switzerland.
Keywords: Adjustable simulink block; Analysis and modeling; General form of mathematical model; Modified quadruple-tank process; Multivariable and interacting process control